Livestock extension message development guidelines - Lemma, Mamusha; Gizaw, Solomon; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2023)
Communication of information and knowledge with farmers and pastoralists is key to creating awareness about challenges and opportunities and inducing behaviour change. Extension services are the main vehicle for providing information, knowledge and advisory services to rural people. Thus, frontline extension agents are the primary advisers and information providers to women and men community members on agriculture, livestock, environment, animal and human health issues. Extension advisors require skill sets that include situation analysis, planning, message development, communication skills and cultural competence. Clarity on why, what, how, when and to whom to communicate messages is vital in providing extension advice. This document provides guidelines for extension (including livestock extension) agents on good communication practices and attributes of good extension messages, including how to develop effective extension messages and materials that can apply to different sectors, such as agriculture, livestock, environment and animal and human health. It is vital for extension agents to understand the benefits and characteristics of good extension messages as one of the components of the communication process.